Pengaruh Kualitas Pelayanan dan Physical Evidence terhadap Loyalitas Pelanggan Onti Coffe - Steviana Al Fitran; Esti Dwi Rahmawati; Triana Triana (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
Fierce rivalry within the food and beverage (F&B) industry drives business operators to consistently enhance the quality of their service while cultivating an appealing physical environment in order to sustain customer loyalty. Maintaining loyal customers has become an essential strategy for ensuring long-term business growth and competitiveness in an increasingly dynamic market. The present study seeks to examine the effect of service quality and physical evidence on customer loyalty at Onti Coffee. A quantitative, associative research design was applied for this purpose. A total of 100 customers were selected as respondents through the purposive sampling technique. Data were gathered by distributing structured questionnaires and subsequently processed using the Statistical Package for the Social Sciences (SPSS) using multiple linear regression analysis. The findings reveal that service quality and physical evidence each exert a positive and significant influence on customer loyalty, both independently and jointly. These results suggest that improving service quality alongside the provision of a comfortable, attractive, and well-maintained physical setting can serve as an effective strategy for reinforcing customer loyalty at Onti Coffee. The findings are also expected to provide practical insights for managers in developing customer-oriented service strategies and creating a more satisfying customer experience.